Early neonatal hypoglycemia in term and late preterm small for gestational age newborns - Lin-Yu Wang; Lin-Yen Wang; Yu-Lin Wang; Chung-Han Ho (Elsevier, 2023)
Background: Neonatal hypoglycemia is a common metabolic occurrence among small for gestational age (SGA) neonates. This study aims to determine the incidence of early neonatal hypoglycemia and confirms the potential risk factors among term and late preterm SGA neonates in a well-baby newborn nursery of a tertiary medical center in Southern Taiwan. Methods: We performed a retrospective medical record review of term and late preterm SGA (birth weight <10 percentile) neonates, born between January 1, 2012 and December 31, 2020, in the well-baby newborn nursery, of a tertiary medical center in Southern Taiwan. Blood glucose monitoring was routinely performed at 0.5, 1, 2, and 4 h of life. Antenatal and postnatal risk factors were recorded. Mean blood glucose level, age of occurrence, symptomatic hypoglycemia, and need for intravenous glucose treatment of early hypoglycemia in SGA neonates were documented. Results: 690 SGA neonates in the nursery met the criteria and were retrospectively enrolled in the study, 358 of whom (51.80%) were male and 332 (48.10%) female. Of 690 enrolled SGA neonates, 134(19.42%) SGA neonates developed hypoglycemia during a well-baby nursery stay. Among these neonates, 97% of early hypoglycemic episodes occur during the first 2 h of life. The lowest blood glucose level was 46.78 ± 11.13 mg/dL, recorded in the first hour of life. Among the hypoglycemic 134 neonates, 26 (19.40%) neonates had to be transferred from the nursery to the neonatal ward and they required intravenous glucose treatment to achieve euglycemia. 14 (10.40%) neonates had symptomatic hypoglycemia. A multivariate logistic regression analysis revealed that cesarean delivery, small head circumference, small chest circumference, and low 1-min Apgar score were significant risk factors for early hypoglycemia in these neonates. Conclusion: Periodic routine blood glucose level monitoring within the first 4 h of life in term and late preterm SGA neonates is required, especially those with cesarean delivery and low Apgar score.